2015
DOI: 10.22610/imbr.v7i3.1149
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Financing Determinants of Islamic Banks in Malaysia

Abstract: Despite commendable growth of Islamic banking on a macro level, impaired financing is an issue among Islamic banks at the micro level. The 2008 Global Financial Crisis shows large credit risk was largely attributable to staff inefficiency. This study investigates the moderating effect of staff efficiency on determinants of credit risk or impaired financing of sixteen Islamic banks in Malaysia over the 2005-2013 periods. The determinants include new variables such as political stability index and corruption ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…It shows that the relationship between credit risk and commercial bank performance is negative and significant. Nor and Ahmad (2015) revealed that impaired NPL financing reduces bank profitability and growth that ultimately impacts the country's economic growth. Berger and DeYoung (1997) illustrate the connections between bank-specific factors and focus on indicators of efficiency and problem loans.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It shows that the relationship between credit risk and commercial bank performance is negative and significant. Nor and Ahmad (2015) revealed that impaired NPL financing reduces bank profitability and growth that ultimately impacts the country's economic growth. Berger and DeYoung (1997) illustrate the connections between bank-specific factors and focus on indicators of efficiency and problem loans.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, the global financial sector has undergone more than 100 crises over the past three decades (Stiglitz & Stiglitz, 2003). Many researchers such as Hassan and Kayed (2009); Nor and Ahmad (2015) argued that the unethical and moral hazard issues such as risk mismanagement, debt default, imprudent mortgage loan, inadequate transparency, human frailty, and complex financial instrument are the major reason behind the crisis. These crises have enforced that ethics issues are linked to the survival of the financial system.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the theory of financial intermediation from the Islamic banking perspective stressed that the Islamic banking is not just intermediaries but also a business entity to run the provided capital by the depositor or capital provider (Nor et al, 2015). In a similar token, Bariah, Hubeis, and Hafidhuddin (2015) quoted Danuwirana (2012) stressing that Islamic human resources are required to have core competence in various areas including functional (expert in Islamic economics, banking operations, finance administrations, financial analysis) and managerial skills.…”
Section: The Moderating Role Of Staff Efficiencymentioning
confidence: 99%
“…There is handful number of research on the moderating role of staff efficiency in financial risk literature. Nor et al (2015) reported high significant level (0.01) of the impact of staff efficiency on reducing impaired financing (credit risk). The authors stressed that banks' management should give identical importance on increasing the role of staff efficiency in managing credit risk.…”
Section: The Moderating Role Of Staff Efficiencymentioning
confidence: 99%
See 1 more Smart Citation